David Fincher interviews - Fincher, David 1962- (Univ. Press of Mississippi, 2014)
"David Fincher (b. 1962) did not go to film school and hates being defined as an auteur. He prefers to see himself as a craftsman, dutifully going about the art and business of making film. Trouble is, it's hard to be self-effacing when you are the director responsible for Se7en, Fight Club, and The Social Network. Along with Quentin Tarantino, Fincher is the most accomplished of the Generation X filmmakers to emerge in the early 1990s. This collection of interviews highlights Fincher's unwavering commitment to his craft as he evolved from an entrepreneurial music video director (Fincher helped Madonna become the undisputed queen of MTV) into an enterprising feature filmmaker. Fincher landed his first Hollywood blockbuster at twenty-seven with Alien3, but that film, handicapped by cost overruns and corporate mismanagement, taught Fincher that he needed absolute control over his work. Once he had it, with Se7en, he achieved instant box-office success and critical acclaim, as well as a close partnership with Brad Pitt that led to the cult favorite Fight Club. Fincher became circumspect in the 2000s after Panic Room, shooting ads and biding his time until Zodiac, when he returned to his mantra that "entertainment has to come hand in hand with a little bit of medicine. Some people go to the movies to be reminded that everything's okay. I don't make those kinds of movies. That, to me, is a lie. Everything's not okay." Zodiac reinvigorated Fincher, inspiring a string of films...The Curious Case of Benjamin Button, The Social Network, and The Girl with the Dragon Tattoo...that enthralled audiences and garnered his films dozens of Oscar nominations"..
Mother from another planet / John H. Richardson -- Mr. Fincher's neighborhood / James Kaminsky -- Seventh Hell / Mark Salisbury -- David Fincher Interview / Iain Blair -- Precocious Prankster who gets a thrill from tripping people up / Ryan Gilbey -- The head master / Jenny Cooney -- Inside out / Gavin Smith -- Twenty-first-century boys / Amy Taubin -- Fight and good fight / Andrew Pulver -- Four walls and a funeral / Ryan Gilbey -- Inside Panic Room: David Fincher, the roundtable interview / Daniel Robert Epstein -- David Fincher Interview / Stephan Littger -- Forget the first two rules of Fight Club / Nev Pierce -- David Fincher of Zodiac / Shawn Levy -- The devil is in the detail / Nev Pierce -- A curious case of friendship / Scott Bowles -- In conversation with David Fincher / Nev Pierce -- David Fincher British Film Institute Interview / Mark Salisbury -- Social Network: Interview with Director David Fincher / Emanuel Levy -- The vultur transcript: an in-depth chat with David Fincher about The social Network / Mark Harris -- Chasing the dragon / Nev Pierce -- Heart of darkness / Brian Raftery -- You better be F-ing serious: David Fincher on Directing / Fincher Fanatic
Includes bibliographical references and index. - Includes filmography
Keywords: Fincher, David -- Interviews; Fincher, David -- 1962-; Geschichte 1962-; PERFORMING ARTS / Individual Director (see also BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts); BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts; Motion picture producers and directors -- United States -- Interviews; Filmregisseur; Regisseur; USA; Biografie; Interview